Respek vir die liturgiese teks: J. Calvyn en J.S. Bach - L. F. Schulze (Acta Theologica)
Despite obvious differences in terms of historical and theological aspects between Calvin and Bach, both share a respect for the priority of the Biblical text in worship.The anomaly between Calvin’s engagement in the versification of the Psalter and Bach’s preference for the literal (rather than a versified) use of the Biblical text (for example in his St. Matthew Passion) is rooted in their common respect for the Word of God originating from the Reformation.